2000
DOI: 10.1016/s0014-5793(00)01910-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of chromophore in the lipid–protein interactions in bacteriorhodopsin–phosphatidylcholine vesicles

Abstract: By fluorescence and phase properties of a 1-acyl-2-[8-(2-anthroyl)-octanoyl]-sn-glycero-3-phosphocholine probe, the influence of the chromophore on the phase transition of bacteriorhodopsin^lipid vesicles was investigated. It was observed that removal of the chromophore led to the down-shifting of the phase transition temperatures. The temperatures corresponding to the beginning and ending of the gel^liquid phase transition were also influenced. This demonstrated that the liquid phase is reached more easily wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Previously, the deuterium exchange and atomic force microscopy (AFM) experiments showed that removal of the retinal induces subtle changes of the tertiary structure and the loops of bR to the more open conformation. , Related to this, the change of protein−lipid interaction by retinal removal was observed in the artificial lipid vesicle system . In this study, this protein−lipid interaction change on the membrane was successfully detected as the difference of the solubility between bR and bO in DDM (Figure ).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Previously, the deuterium exchange and atomic force microscopy (AFM) experiments showed that removal of the retinal induces subtle changes of the tertiary structure and the loops of bR to the more open conformation. , Related to this, the change of protein−lipid interaction by retinal removal was observed in the artificial lipid vesicle system . In this study, this protein−lipid interaction change on the membrane was successfully detected as the difference of the solubility between bR and bO in DDM (Figure ).…”
Section: Discussionsupporting
confidence: 53%
“…7,8 Related to this, the change of protein-lipid interaction by retinal removal was observed in the artificial lipid vesicle system. 29 In this study, this protein-lipid interaction change on the membrane was successfully detected as the difference of the solubility between bR and bO in DDM (Figure 4). Interestingly, the bR solubility was also increased by the cyclic and milliseconds order of structural change after light absorption ( Figure 5).…”
Section: Solubility Of Bleached Br In Ddmmentioning
confidence: 66%
See 2 more Smart Citations
“…31 The incorporation of fluorinated retinal analogues with changed shape and altered electronic properties into the binding site of bR (or bR mutant, D96N) was used to strengthen the feedback between the protein surrounding and chromophore in bRs. 22,32 Fluorine atom is a highly electronegative atom. Its incorporation into chromophore structure causes enlargement mostly of electrostatic interactions with charged amino acids (although steric interactions cannot be excluded).…”
Section: Introductionmentioning
confidence: 99%